Pengaruh Pendekatan Pembelajaran Konstruktivisme dan Self-Efficacy Siswa terhadap Kemampuan Komunikasi Matematis Siswa - Amin Asri Yati; Jefri Marzal; Yantoro Yantoro (Didaktik Matematika, 2018)
This study concerned on the influence of constructivism and student self-efficacy approach to mathematical communication. The ability of mathematical communication and self-efficacy of student-controlled students is very important for students. This research sought to examine (1) the influence of learning approach of constructivism to mathematical communicative ability, (2) the influence of student self-efficacy toward student's mathematical communication ability, (3) influence of constructivism and student self-efficacy approach to students' mathematical communication ability. This is a quantitative research employing the pretest-posttest non-equivalent control group design, the population in this study is all Year 7 students of junior high school. Data collection was done by student mathematical communication skills test and student self-efficacy attitude scale. This study found that the use of constructivism and self-efficacy approach significantly influence students' mathematical communication skills and there is no interaction between students mathematical communication skills and self-efficacy using the constructivism learning approach.